2004
DOI: 10.1177/0898264303260446
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness and Disability among Elders in Developing Countries

Abstract: Documenting the extent of psychiatric disorder among elders in developing societies sensitizes health planners to the growing reality of aging in their societies and the need for expanded physical and psychiatric health care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Psychiatric epidemiology in Nepal has been extremely limited; one other study found a prevalence rate of 18.4% of any mental disorder in a rural community (Subedi et al 2004; Tausig et al 2004). This was a Janajati (not caste-Hindu) group on a motorable road in a tourist region with a greater human development index than Jumla.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric epidemiology in Nepal has been extremely limited; one other study found a prevalence rate of 18.4% of any mental disorder in a rural community (Subedi et al 2004; Tausig et al 2004). This was a Janajati (not caste-Hindu) group on a motorable road in a tourist region with a greater human development index than Jumla.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these studies are Epidemiological field surveys [2][3][4][5] , hospital based outpatient studies [6][7][8][9] as well as inpatient studies [10][11][12] . In the present decade there is resurgence of geropsychiatric study reports from Nepal [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…It is within this context that NSSW is working. Research with activists working in the field of ageing in Nepal stress there is an acute need for trained social workers who can work with elders in general and more specifically with abused elders and those with disabilities and mental health issues (Subedi, Tausig, Subedi, Broughton, & Willaims-Blangero, 2004). Also in order to make professional social work services available to the 30 million people of Nepal there is a growing need for institutions that can offer social work education and training programmes throughout Nepal (Nikku, 2009(Nikku, , 2010(Nikku, , 2011.…”
Section: Social Work In Nepal and In The Field Of Active Ageingmentioning
confidence: 98%